Evidence-based geology as a basis for improving the efficiency of innovative design of the development of Tengizchevroil oil fields - Nursaule Tauova (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2022)
The article's main purpose is to study the method of storing sulfur in solid form in a large block at Tengizshevroil deposits and dispose of sulfur residues. Thus, we have to admit that, in this case, the evaluation of the effectiveness of the innovation at the stage of its development was performed incorrectly, and thus the consumer was misled. As a rule, the production activities of enterprises are planned according to the average parameters that are not known reliably in advance and can change randomly. At the same time, a situation with sharp changes in these indicators is extremely undesirable because this means the threat of loss of control. The smaller the deviation of the indicators from the average expected value, the greater the stability. That is why the statistical method based on mathematical statistics has become the most widespread in assessing investment risk. A more complex mathematical apparatus (regression and correlation analysis, simulation modeling methods) allows for a deeper analysis of the risk and its causes. The discrepancy between modern progressive technical capabilities and archaic